PENGARUH LIVE STREAMING TIKTOK, POTONGAN HARGA, DAN CELEBRITY ENDORSEMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE (Studi Kasus Pada Produk Skintific di Lamongan) - Aifa Nadia Rohmah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the impact of TikTok live streaming, price discounts, and celebrity endorsements on purchasing decisions for Skintific skincare products in Lamongan. In the fast-paced digital era, social media, particularly TikTok, plays a crucial role in influencing consumer decisions. This platform offers features such as live streaming, which has become an effective marketing tool, while price discounts and celebrity endorsements further enhance product image in the eyes of consumers. This research adopts a quantitative method with a descriptive approach, involving 155 respondents from the FEB UNISLA in Lamongan. The results indicate that all three factors—live streaming, price discounts, and celebrity endorsements—have a positive and significant impact on purchasing decisions. The multiple linear regression model reveals that price discounts have the greatest impact on purchasing decisions. This study provides valuable insights for companies to leverage social media, particularly TikTok, to optimize skincare product marketing through innovative promotional techniques.